Sosialisasi Dan Coaching Clinic Perwasitan Tenis Lapangan Pada Mahasiswa Program Studi PENJAS Universitas Megarezky - Ilham Budiutama; Budyanita Asrun; Andi Hasman Husada (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
Socialization of Coaching Clinic Tennis Court Supervision for Students of FKIP Study Program of Megarezky University is a form of community service from lecturers of the faculty of sports science in order to carry out the tri dharma of higher education. by providing short training provided by lecturers who are also nationally certified court tennis coaches. Students who take part in this training are expected to be able to apply the knowledge of court tennis supervision obtained from this coaching clinic event so that the goal of improving the quality of matches can be achieved. This socialization and coaching clinic event consists of 2 sessions, namely a theory session, namely the provision of game rules theory and court tennis supervision by lecturers to students who follow which is carried out indoors, and a practical session which is the application of the guardianship theory that has been given in the field. The trainees were very enthusiastic about participating in this coaching clinic because they were faced with direct practice with the expert. By implementing this coaching clinic, it is hoped that it will be able to improve the quality of students' understanding of the rules of the game and tennis court supervision